2008
DOI: 10.1021/jp8003739
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-Temporal Perturbation of the Dynamics of the Ferroin Catalyzed Belousov−Zhabotinsky Reaction in a Batch Reactor Caused by Sodium Dodecyl Sulfate Micelles

Abstract: The effects of the anionic surfactant sodium dodecyl sulfate (SDS) on the spatio-temporal and temporal dynamics of the ferroin-catalyzed Belousov-Zhabotinsky (BZ) reaction have been studied over a wide surfactant concentration range. For the first time, investigations were performed also for unstirred systems. The presence of SDS in the reaction mixture influences the oscillatory parameters to an extent that significantly depends on the surfactant concentration. The trend of the wave speed V upon the increasin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 39 publications
3
31
2
Order By: Relevance
“…In fact, after an initial decrease, the average oscillation period starts to grow when [DPPC] > 2.5%, even if it never reaches the initial value (Figures 4 and 5). A similar behavior has been found in the past for other surfactants [12,13].…”
Section: Resultssupporting
confidence: 89%
“…In fact, after an initial decrease, the average oscillation period starts to grow when [DPPC] > 2.5%, even if it never reaches the initial value (Figures 4 and 5). A similar behavior has been found in the past for other surfactants [12,13].…”
Section: Resultssupporting
confidence: 89%
“…The concentration profiles are obtained by solving in one spatial dimension (z) the diffusion equations with the characteristic diffusion matrix of the ME (see Sec. III A) D ¼ 0:6 7:8 À0:01 1:3 Â 10 À6 cm 2 s À1 ; (11) while the density distribution is found according to Eq. (10), using the solutal expansion coefficients measured experimentally (see Sec.…”
Section: Density Profiles Analysismentioning
confidence: 99%
“…The dynamics of the well known BZ 1,2 chemical oscillator, in particular, has been studied with many self-assembled matrices 3 and structured media 4 including gels and hydrogels, 5-8 micelles, [9][10][11][12][13][14] polymers, [15][16][17][18] and lipid vesicles and aggregates. [19][20][21][22][23][24] Particularly important from the pattern formation viewpoint, the AOT water-in-oil reverse MEs, are probably the most thoroughly studied system in combination with the BZ reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Even an addition of nonreacting chemical species induces effective changes in the pattern dynamics internally. For example, self‐assembled aggregates of surfactants have been employed to compartmentalize crucial intermediates to affect the temporal dynamics of the BZ reaction . The perturbation experiments often give a new insight about a reaction mechanism in addition to controllability of the pattern formation.…”
Section: Introductionmentioning
confidence: 99%
“…Surfactant‐forming micelles (direct and reverse) revealed to be very fascinating and promising due to their ability to selectively interact via electrostatic and/or hydrophobic interactions with the reaction substrates or products present in the medium . The works of Liveri et al and others have exhaustively demonstrated the effects of different types of self‐assembled additives such as surfactants and/or polymers on the oscillatory parameters of the BZ oscillatory reaction such as an induction period and oscillation time period . However, the literature has scarcely highlighted the role of mixed surfactant systems on the dynamics of the BZ oscillatory reaction.…”
Section: Introductionmentioning
confidence: 99%